Қарақалпақ әдебиятында импровизация дәстүриниң изертлениў мәселеси - Матимов, К.Г (FAN va JAMIYAT, 2020)
This article discusses the theoretical foundations of improvisational traditions in Karakalpak literature, the stages of formation, de- velopment and research issues in modern Karakalpak literary criticism based on the research of N. Davkaraev, K. Aimbetov, A. Pakhratdinov, K. Allambergenov. And also, it is said about the occurrence of the phenomenon of improvisation, the stages of the for- mation of the Karakalpak oral folk art, that it originates from the legacy of zhyrau poets of the early period and continues in today's
Keywords: импровизация; анъана; халқ оғзаки ижоди; жиров-шайир